Effect of thermal treatment on dielectric properties of 0.8Pb(Zr 1/2Ti1/2)O3 - 0.2Pb(Co1/3Nb 2/3)O3 ceramics - A. Prasatkhetragarn (2018)
A combination between piezoelectric (Pb(Zr1/2Ti 1/2)O3; PZT) and relaxor ferroelectric (Pb(Co 1/3Nb2/3)O3; PCN) materials with a formula of 0.8Pb(Zr1/2Ti1/2)O3 - 0.2Pb(Co 1/3Nb2/3)O3 has been prepared with solid-state reaction (the columbite-wolframite precursor method). This specific composition was selected for investigation because it is close to a morphotropic phase boundary (MPB) between the tetragonal and pseudo cubic phases. The phase formation behavior and microstructure were studied using x-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. The dielectric properties of the compound were measured and discussed. The ceramics were also heat-treated at 800 °C. The results showed that the dielectric properties of the compound depended significantly on the heat treatment conditions. Most importantly, this study showed that the addition of PCN can improve the dielectric characteristics in PZT ceramics. © 2008 Trans Tech Publications, Switzerland.